Debate to Cultivate Critical Thinking and Communication Skill - Mokhammad Nizzam; M. Miftachul Huda; Dian Anggraini; Umi Kholidah (CV. Edutechnium Indonesia, 2023)
Parliementary debate has been a major trend across the globe and conducted to get well-arranged arguments in many circumstances. The mushrooming contests of debating around the globe has shown that this activity positively impacts learners’ skills,i.e. critical thinking and communication skills. Geared under qualitative approach, this article aims to investigate how parliementary debate can cultivate their critical thinking and communication skills. The data were collected via semi-structured observation and interview in an English debating club at a private Islamic senior high school involving 6 participants and 2 coaches. The findings revealed that debate offers several distinct features to significantly improve students’ two aforementioned skills.